Japanese language students’ perceptions on online Nihongo Partner Program / Nur Anisah Tan Abdullah …[et al.] - Tan Abdullah, Nur Anisah; Yean, Choong Pow; Shaharuddin, G. Sharina; Abdul Rashid, Nor Rasimah (Universiti Teknologi MARA, 2021)
The Nihongo Partner (NP) Program at University of Technology MARA, Shah Alam (UiTM) is a Japanese student exchange program was first organized by the Japan Foundation in 2017. The main objective of the NP Program is to involve Japanese students from two universities in Tokyo sent to assist lecturers for 6 weeks in teaching and learning as well as organizing activities with UiTM students outside of lecture hours. The pandemic has forced the face-to -face Nihongo Partner (NP) Program to be postponed. Japanese language lecturers have converted the program to virtual engagement so that it can be utilized by Japanese students and Japanese language students in UiTM. Thus, the virtual NP program (NPAT) was introduced. After the program was implemented, a quantitative study was conducted on 487 students involved with the program. Responses from 465 students were used to collect data related to students' perceptions of the strengths and weaknesses of the program and suggestions for improvement. The data were analysed using a five (5) Likert scale mean interpretation. As for the data on "suggestions for improvement" were collected under the category for "further action". The finding indicated positive respondents on the program and has benefited their Japanese language learning. NPAT was also found to improve speaking skills with correct pronunciation and intonation as well as increased speaking opportunities and students' confidence to communicate with native speakers or their peers. The findings also illustrated that some respondents are embarrassed or afraid to make mistakes. The researcher is in the opinion that this could be a potential area of research.